Food restriction but not fish oil increases fertility in hens: role of RARRES2?. Issue 4 (April 2018) - Mellouk, Namya; Ramé, Christelle; Delaveau, Joël; Rat, Christophe; Marchand, Maxime; Mercerand, Frédéric; Travel, Angélique; Brionne, Aurélien; Chartrin, Pascal; Ma, Linlin; Froment, Pascal; Dupont, Joëlle
Abstract : Overfed hens selected for their rapid growth become fatter and develop reproductive disorders. Herein, we aimed to demonstrate that food restriction leading to a weight reduction and/or a supplementation with fish oil may be effective in preventing reproductive disorders through the regulation of adipokine expression in broiler hens. This study included four groups of food restricted (Rt) or ad libitum hens (Ad, feeding at a rate 1.7 times greater than Rt hens) supplemented or unsupplemented with fish oil (1%). The Rt diet significantly increased plasma chemerin (RARRES2) levels during the laying period, delayed sexual maturity by one week and improved egg quality and fertility. These effects were associated with higher progesterone production in response to IGF1 (or LH) in cultured granulosa cells and in vivo egg yolk, as compared with Ad hens. Fish oil supplementation had similar effects to the Rt diet on progesterone ( P < 0.05), but without any effect on fertility. Using RT-PCR, we found that RARRES2 levels were lower in theca cells of Rt hens and NAMPT levels were increased by the fish oil supplementation. A significant positive correlation between RARRES2 expression in granulosa cells and the weight of F1 preovulatory follicle was observed, as well as a negative correlation of plasma RARRES2 levels with hatchability. Thus, food restriction but not fish oil supplementation improved fertility, and this was associated with variations in RARRES2 plasma and ovarian expression in hens.